2009
DOI: 10.1111/j.1471-4159.2009.05916.x
|View full text |Cite
|
Sign up to set email alerts
|

AMPK in the brain: its roles in energy balance and neuroprotection

Abstract: AMP-activated protein kinase (AMPK) senses and maintains energy balance in peripheral tissues. When energy is deficient, AMPK activation leads to altered cellular metabolism and gene expression to inhibit anabolic processes, stimulate catabolism, and restore ATP. The CNS integrates diverse central and peripheral signals to maintain homeostasis. CNS AMPK is shown to have important, but complex roles in energy balance. CNS neurons sense their own energy needs, while some also integrate neuro-humoral signals to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
186
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(191 citation statements)
references
References 77 publications
(149 reference statements)
5
186
0
Order By: Relevance
“…Once activated, AMPK promotes catabolic pathways to generate more ATP, and inhibits anabolic pathways, thus allowing for adaptive changes in growth and metabolism under low energy conditions 23. Emerging evidence indicates that AMPK can be activated by metformin in the brain, exerting a neuroprotective role in response to energy depletion through maintaining cellular energy homeostasis,24, 25, 26 promoting mitochondrial biogenesis,27 and increasing brain‐derived neurotrophic factor expression to promote neuronal survival 28. Recently, autophagy has been proposed as a downstream target of AMPK, and AMPK‐induced autophagy activation protects against ischemic injury to peripheral tissue injury29, 30, 31 as well as ischemic brain injury 32.…”
Section: Introductionmentioning
confidence: 99%
“…Once activated, AMPK promotes catabolic pathways to generate more ATP, and inhibits anabolic pathways, thus allowing for adaptive changes in growth and metabolism under low energy conditions 23. Emerging evidence indicates that AMPK can be activated by metformin in the brain, exerting a neuroprotective role in response to energy depletion through maintaining cellular energy homeostasis,24, 25, 26 promoting mitochondrial biogenesis,27 and increasing brain‐derived neurotrophic factor expression to promote neuronal survival 28. Recently, autophagy has been proposed as a downstream target of AMPK, and AMPK‐induced autophagy activation protects against ischemic injury to peripheral tissue injury29, 30, 31 as well as ischemic brain injury 32.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothalamic AMPK is also involved in feeding regulation and food intake by regulating the AMPK-ACC-Malonyl-CoA-CPT1 axis (ACC: acetyl-CoA carboxylase; CPT1: carnitine palmitoyltransferase 1) [91][92][93][94]. A study using the CT1-1 cell line reported that the protein level of phosphor-AMPK (pAMPK) is activated by the H 1 R antagonist chlorpheniramine, while it is blocked by histamine [95].…”
Section: The Role Of Hypothalamic H 1 R-ampk Signalling In Sga-inducementioning
confidence: 99%
“…A rise in AMP levels or an increase in the AMP/ATP ratio signals declining energy stores, activating AMPK (see review by Li and McCullough 2010). Although responsive to ATP depletion (increased AMP/ATP ratio), AMPK is also activated by related stimuli such as exercise, starvation, hypoxia, cellular pH, and redox status (Ronnett et al 2009). Ischemic brain injury involves a complex sequence of excitotoxic and oxidative events, including cellular energy depletion, disrupted protein synthesis, and apoptosis, etc.…”
Section: Introductionmentioning
confidence: 99%